Insulinoma of Pancreatic Head Localized by Intra-Arterial Calcium Stimulation with Hepatic Venous Sampling - Wong, Siong Hu; Omar, Julia; Yusof, Noor Azlin Azraini Che Soh (Bangladesh Journal of Medical Science, 2021)
Hypoglycemia is a common medical emergency. Insulinoma, a rare pancreatic endocrine tumour is the most common cause of hypoglycemia in patients without systemic illness. Most insulinomas are small, solitary and benign, which can be treated effectively by surgical removal of the tumour. Diagnosis is based on clinical features, laboratory tests and radiological investigation to localize the tumour. However, small size of this tumour leads to difficulty in localization of the disease, especially in occult insulinoma. Intra-arterial calcium stimulation with hepatic venous sampling can be utilised for preoperative localization of the tumour. We hereby present a case of a 33-year-old woman presenting with history of recurrent hypoglycemic symptoms and morbid obesity. A thorough history, clinical examination and laboratory investigation including prolonged fasting test were conducted and diagnosis of insulinoma was made. Intra-arterial calcium stimulation with hepatic venous sampling was carried out and revealed localization of insulinoma at pancreatic head. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.216-219